Diagnosis of Thin-Capped Fibroatheromas in Intravascular Optical Coherence Tomography Images: Effects of Light Scattering. (July 2016) - Phipps, Jennifer E.; Hoyt, Taylor; Vela, Deborah; Wang, Tianyi; Michalek, Joel E.; Buja, L. Maximilian; Jang, Ik-Kyung; Milner, Thomas E.; Feldman, Marc D.
Abstract : Background—: Intravascular optical coherence tomography (IVOCT) images are recorded by detecting light backscattered within coronary arteries. We hypothesize that non–thin-capped fibroatheroma (TCFA) causes may scatter light to create the false appearance of IVOCT TCFA. Methods and Results—: Ten human cadaver hearts were imaged with IVOCT (n=14 coronary arteries). IVOCT and histological TCFA images were coregistered and compared. Of 21 IVOCT TCFAs (fibrous cap <65 μm, lipid arc >1 quadrant), only 8 were true histological TCFA. Foam cell infiltration was responsible for 70% of false IVOCT TCFA and caused both thick-capped fibroatheromas to appear as TCFA, and the appearance of TCFAs when no lipid core was present. Other false IVOCT TCFA causes included smooth muscle cell–rich fibrous tissue (12%) and loose connective tissue (9%). If the lipid arc >1 quadrant (obtuse) criterion was disregarded, 45 IVOCT TCFAs were identified, and sensitivity of IVOCT TCFA detection increased from 63% to 87%, and specificity remained high at 92%. Conclusions—: We demonstrate that IVOCT can exhibit 87% (95% CI, 75%–93%) sensitivity and 92% specificity (95% CI, 86%–96%) to detect all lipid arcs (both obtuse and acute, <1 quadrant) TCFA, and we also propose new mechanisms involving light scattering that explain why other plaque components can masquerade as TCFA and cause low positive predictive value of IVOCT for TCFA detection (47% for obtuse lipid arcs). Disregarding the lipid arc >1 quadrant requirement enhances the ability of IVOCT to detect TCFA. Abstract : Supplemental Digital Content is available in the text.